Association Between Perforating Scleral Vessel and Myopic Maculopathy: A Cross-Sectional Study of a Chinese Cohort - Yu, Huimin; Sun, Jinfu; Luo, Huan; Wang, Zhitao; Sun, Xufang (Frontiers in Medicine, 2022)
Purpose: To investigate the association between perforating scleral vessel (PSV) and different types of myopic maculopathy (MM) in a highly myopic population. Methods: 188 highly myopic eyes (117 participants) were enrolled. Each participant underwent detailed history taking and ocular examinations. Based on fundus photographs and optical coherence tomography, patients were subdivided into non-MM group and MM group. Based on a new classification system (ATN), MM cases were classified as myopic atrophy maculopathy (MAM), myopic tractional maculopathy (MTM), and myopic neovascular maculopathy (MNM). The number of PSV and the macular choroidal thickness (mChT) were measured individually. Results: Compared with non-MM group, patients with MM were characterized by older age (48.40 vs. 32.34; p=<0.001), longer axial length (AL, 29.72 vs. 27.75, p=<0.001), thinner mChT (52.90 vs. 122.52; p=<0.001) and lower PSV counts (6.73 vs. 9.47, p=<0.001). The non-MM group had higher PSV counts in total area (0-9mm, 9.47 vs. 6.73, p=<0.001) and perifovea area (3-9mm, 7.25 vs. 4.71, p=<0.001) relative to the MM group. Univariate and multivariate analysis showed that PSV count had no association with MAM (p=0.2419) and MTM (p=0.5678). Total PSV count (OR 0.78, 95% CI 0.64-0.95, p=0.0149) and perifovea PSV count (OR 0.80, 95% CI 0.65-0.98, p=0.0299) were both protective factors for MNM. Stratified analysis revealed that in groups with AL<28mm, or mChT ≥100 μm, or eyes with cilioretinal artery, PSV count had no significant association with MNM. Conclusion: Higher PSV counts in perifovea area (3-9mm centered fovea) and total area (0-9mm centered fovea) were protective factors for MNM, whereas PSV count had no association with MAM and MTM. These findings may provide novel insights into the mechanisms of pathologic myopia.